Provision Of Coconut Water As Good As Packed Coconut Water And Isotonic Beverages On Hydration Status In Football Athlete (Journal of Physical Education Health and Sport, 2022)
The purpose of this study was to analyze differences in the hydration status of subjects who used coconut water, packaged coconut water, and isotonic drinks like sports drinks. The research design used in this study was a cross-over design. The test was carried out 4 times a week with a washout period of 2x24 hours. In each test, athletes were asked to jog on a treadmill for 40 minutes at a 5.6 km/hour speed and a slope of 5%. Drinks were given as much as 150 ml in the 15th minute and 30th minute while jogging on the treadmill. Measurement of urine-specific gravity using a refractometer and urine color table was performed before and after jogging on a treadmill to assess the hydration status of the subject. Based on the results of this study, it can be concluded that coconut water is as good as packaged coconut water and isotonic drinks in maintaining the hydration status of athletes, as seen from the urine specific gravity and urine color table. However, coconut water contains antioxidants that isotonic drinks don’t, therefore coconut water has the potential to be sports drink because it can maintain hydration status and minimize oxidative stress resulting from exercise if treated properly with the addition of sodium